Using Analytical Hierarchy Process (AHP) (Global Journal of Management and Business Research, 2015)
This study comes to Use the Analytic Hierarchy Process (AHP) approach to build shares portfolio in kingdom of Bahrain shares' market. So that, we want to find out to what extent the Analytical Hierarchy Process approach is helpful taken in the account the importance of the investment decision to the investors as individuals or fund manager. We perform this assessment depending on the information of Bahrain stock market activities' handbook and some experts who have good experience in financial planning and some colleagues in university who are teaching financial and investment decision courses. The results demonstrated that (AHP) can help the decision maker to rank the sectors of the stock market according to their relative importance.
Keywords: analytical hierarch process (AHP); pair-wise comparisons; multi-criteria decision making